2020
DOI: 10.21470/1678-9741-2019-0445
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral vs. Central Cannulation in Cardiac Reoperations: Technical Considerations and Outcomes

Abstract: Objective To compare peripheral and central cannulation techniques in cardiac reoperation. Methods This retrospective study included 258 patients undergoing cardiac reoperation between January 2013 and July 2018. Patients were divided into two groups according to the cannulation type. The first group included 145 (56.2%) patients operated with standard central cannulation through aorta and right atrium or bicaval cannulation. In this group, cardiopulmonary bypass was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…In the whole cohort and propensity-matched cohorts, there was no difference in early mortality between the groups. Like our study, Ata et al [ 5 ] , Luciani et al [ 4 ] , and Kuralay et al [ 6 ] found no difference between central cannulation technique and peripheral cannulation technique in terms of early mortality. However, Brown et al.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the whole cohort and propensity-matched cohorts, there was no difference in early mortality between the groups. Like our study, Ata et al [ 5 ] , Luciani et al [ 4 ] , and Kuralay et al [ 6 ] found no difference between central cannulation technique and peripheral cannulation technique in terms of early mortality. However, Brown et al.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, detailed preoperative demographic characteristics that may affect postoperative acute renal failure were not given and it was not clearly discussed why acute renal failure was less common in the peripheral cannulation group. Other studies by Ata et al [ 5 ] , Kuralay et al [ 6 ] , and Kindzelski et al [ 9 ] found no difference between the central cannulation and the peripheral cannulation technique in terms of postoperative acute renal failure. To the best of our knowledge, this is the first study to demonstrate that performing CPB via peripheral cannulation increases acute renal failure during cardiac reoperations.…”
Section: Discussionmentioning
confidence: 93%
“…As known, if root enlargement is required in aortic valve surgery, exposure of the aortic root becomes a very important issue [3]. In minimally invasive cardiac surgery procedures, cannulation may also be performed via the peripheral vessels; on the other hand, completing the entire surgical procedure from a single incision has more satisfying clinical results [4].…”
mentioning
confidence: 99%